Advanced materials for sodium ion storage - Rajagopalan, Ranjusha; Zhang, Lei (Researcher in energy storage materials) (Boca Raton : CRC Press, 2020)
Globally, lithium ion batteries (LIBs) are leaders in the energy storage sector but there are concerns regarding load leveling of renewable energy sources as well as smart grids and limited availability of lithium resources resulting in cost increase. Therefore, sodium ion batteries (SIBs) are being researched as next-generation alternatives to LIBs due to their similar sustainability and electrochemistry. This book mainly focuses on the current research on electrode materials and proposes future directions for SIBs to meet the current challenges associated with the full cell aspect. Further, it provide insights into scientific and practical issues in the development of SIBs.
OCLC-licensed vendor bibliographic record.
Keywords: Sodium ion batteries; TECHNOLOGY -- Material Science; TECHNOLOGY -- Electronics -- General; SCIENCE -- Chemistry -- Industrial & Technical